MANAJEMEN KURIKULUM DI MADRASAH TSANAWIYAH - Mahmud (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2021)
Curriculum management is a process carried out to achieve learning objectives that emphasize efforts to foster the learning process in schools so that it can run smoothly. Schools are the spearhead of the implementation of the curriculum, both national curriculum and local content, which is realized through the teaching and learning process to achieve national, institutional, curricular and instructional education goals. The scope of curriculum management includes planning management, curriculum implementation management, supervision of curriculum implementation, monitoring and assessment of curriculum and curriculum improvement. The principles of curriculum management are: relevance, flexibility, continuity, practicality and efficiency, effectiveness, productivity, democracy, cooperation, and leads to the vision, mission and goals of the school. The function of curriculum management consists of: (a) Increasing the efficiency of the use of curriculum resources, (b) Increasing equity, (c) Increasing the relevance and effectiveness of learning, (d) Increasing the effectiveness of teacher performance and student activities, (e) Increasing the efficiency and effectiveness of the teaching and learning process, and (f) Increasing community participation.